Integrated Transcriptomic and Proteomic Analyses Reveal Molecular Mechanism of Response to Heat Shock in Morchella sextelata - Jiexiong Zhang; Yanxia Li; Yifan Mao; Yesheng Zhang; Botong Zhou; Wei Liu; Wen Wang; Chen Zhang (Journal of Fungi)
Morels (Morchella spp.), as one of the rare macroascomycetes that can be cultivated artificially, possess significant economic and scientific values. Morel cultivation is highly sensitive to elevated temperatures; however, the mechanisms of their response to heat shock remain poorly understood. This study integrated transcriptomic and quantitative proteomic analyses of two M. sextelata strains with different thermotolerance (labeled as strains C and D) under normal (18 °C) and high temperature (28 °C) conditions. From over 9300 transcripts and 5000 proteins, both consistency and heterogeneity were found in response to heat shock between the two strains. Both strains displayed a capacity to maintain cellular homeostasis in response to heat shock through highly expressed cell wall integrity (CWI) pathways, heat shock proteins (HSPs), and antioxidant systems. However, strain D, which exhibited stronger thermotolerance, specifically upregulated the ubiquitin ligase Rsp5, thereby further promoting the expression of HSPs, which may be a key factor influencing the thermotolerance difference among M. sextelata strains. A conceptual model of the heat shock adaptation regulatory network in M. sextelata was proposed for the first time; the results provide novel insights into the thermotolerance response mechanisms of macroascomycetes and valuable resources for the breeding enhancement of thermotolerant morel strains.